Effective English Learning and Character Education for Young Learners through Animated Video of Indonesian Folklore - Silvia Ade Yusfika (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
The objective of this study is to determine the effectiveness of learning English for junior high school students on local Indonesian literature in English, listening and understanding the content of English language skills based on the popular Indonesian folktale "Timun Emas" uploaded on Andree Rivan Kurniawan's YouTube channel. This study was conducted at State Junior High School (SMP) of 5 Rakit Kulim from August to October 2021 for 20 of seventh grade junior high school students and 26 of the eighth grade students. Based on the results of this study, the values of character education implied in the Timun Mas video story were religious, honest, creative, independent, curious, communicative, hardworking, peace-loving, socially caring, and responsible. The results of this research on the effectiveness of YouTube's animated video learning media reveal that students maintain a positive attitude about learning English through animated videos. Students stated that animated films not only help them improve their listening and speaking skills, but also aid them in learning English vocabulary and sentence structure. This study's findings also imply that animated movies provide junior high school English teachers with extensive English vocabulary and sentence structures, as well as boost learning through engaging activities in English teaching.